Multisensory nature-based Recharge Rooms’ effect on healthcare workers in a multicenter study - Cooke, Lily; Fiorentino, Arianna; Sawyer, Abbey; Dangayach, Neha S.; Sharples, Scott; Szabo, Rena; Hamilton, B. Wade; Cortes, Mar; Putrino, David (Frontiers in Psychology, 2026)
BackgroundHealthcare workers frequently experience significant levels of stress impacting wellbeing and performance. A previous single site study showed multisensory, naturalistic “Recharge Rooms” were associated with a self-reported improvement in stress across healthcare workers. Subsequently, rooms were constructed at multiple hospitals across the country to assess their effects in a multi-site study.ObjectivesTo investigate the association between the Recharge Rooms and self-reported stress levels, alertness, and mood of healthcare workers in multiple health centers.MethodsUnderutilized spaces across 18 US hospitals were converted into Recharge Rooms using video projections of nature landscapes, silk imitation plants, essential oil diffusers, low lighting, music, and nature sounds to create an immersive atmosphere. Healthcare staff had 24/7 access to the rooms. Stress, hopefulness, and alertness were assessed pre- and post-experience on a 0–100 scale with 100 representing “extreme” and 0 being “not at all.”ResultsOf 739 healthcare workers who scheduled time in the rooms, 563 (76%) completed the survey. Average self-reported stress scores decreased from 63.2 to 25.8 (59.1% reduction, p < 0.0001). In addition, the average self-reported hopefulness and alertness increased by 29.6% and 35.1% after a session, respectively (p < 0.0001).DiscussionThe Recharge Rooms were well-received and associated with immediate, self-reported reductions in perceived stress. The self-reported improvement in perceived stress, mood, and alertness were promising results of this multisite, survey-based evaluation of the technology. Controlled trials using validated instruments are necessary to confirm these findings, assess long-term outcomes, and to better understand the physiological effects of this employee wellness intervention.